DRIVERS OF ECONOMIC DEPENDENCE ON WOOD FUEL IN RURAL SOUTHERN ETHIOPIA: A CASE IN ABELA ABAYA DISTRICT. - Deginet Berhanu; Biruk Birhan; Gemedo Furo; Gezahegn Seyoum (Big Data in Agriculture)
In many parts of the world, firewood and charcoal are used as wood fuel by approximately 2 billion people. Wood fuel consumption in Africa, specifically in Ethiopia is quite high. However, there is limited information on the socio-economic and institutional factors that influence wood fuel extraction in the dry land regions of Ethiopia. To address this gap, the current study aimed to examine the determinants of wood fuel production among rural households in the Abela Abaya District of Southern Ethiopia. Using snowball and simple random sampling techniques, data were collected from a total of 160 respondents (80 producers and 80 non-producers) from four kebeles in the district. The collected data was analyzed by using descriptive statistics and binary logistic model was employed to examine the factors influencing wood fuel extraction. The study found that wood fuel production is an important economic activity in the area, with tree species named locally Bedena being the most preferred for firewood and charcoal making. Wood fuel production was regarded as the most favourable primary means of making a living among the participants, despite the fact that it has a negative impact on the environment. The findings suggest that crop farming, alternative income sources, tree species, and market access are significant factors that affect wood fuel extraction. The findings of the study have the potential to provide policymakers with valuable insights into the development of effective energy and forest policies, which can promote sustainable wood fuel extraction practices while ensuring the preservation of the environment for future generations.